Mikroenkapsulasi Metronidazol Dengan Polimer Hpmc Menggunakan Metoda Penguapan Pelarut - Auzal Halim; Reni Daniati; Rina Wahyuni (Jurnal Farmasi Higea, 2013)
Microencapsulation of metronidazole using HPMC as a polymer by solvent evaporation method had been studied. Microcapsulhad been made into3formulation with 3 ratio variation between Metronidazole and HPMC, 1:1; 1:1.5; 1:2. Microcapsules were analyzed by SEM, DTA, FT-IR, particle sized distribution and dissolution profile. Microcapsules were white to slightly yellow and almost perfectly spherical.Disolution profiles of microcapsules showed that the greater amount of HPMC gave the slower release ofMetronidazole. Dissolution kinetics of microcapsule allowedHiguchi equation, where the realese of Metronidazole  from microcapsules were controlled by diffution process.